Syntactic and semantic features of English non-finite clauses in "The adventures of Tom Sawyer" by Mark Twain with reference to their Vietnamese translation equivalents / Duong Tan Phong; Supervisor: PhD Nguyen Thi Van Dong - Duong, Tan Phong
One of the things that should be learned by the English students is grammar. There are so many topics to be mastered by the students, one of which is the non-finite clauses. In order to help Vietnamese learners of English to master English non-finite clauses, we would like to choose the thesis Syntactic and semantic features of English non-finite clauses in “The adventures of Tom Sawyer” by Mark Twain with reference to their Vietnamese translation equivalents. This study focuses on the syntactic and semantic features of on-finite clauses in English and Vietnamese. It is investigated with the hope of finding out the similarities and differences between the non-finite clauses’ form in both languages and suggesting practical applications to the process of teaching and learning English as a foreign language in Vietnam. Data used for analysis in this study were collected from “The adventures of Tom Sawyer” story by Mark Twain and some literary works. To carry out this research, the writer used descriptive, qualitative, quantitative and contrastive methods. The result of the study illustrates the fact that Vietnamese and English native speakers are similar in the choice of non-finite clauses as the prominent element in sentences. However, the structures of non-finite clauses are quite different between two languages. Hopefully, the finding of this study can, to some extent, be suggested as a referential materials for Vietnamese students and teachers of English in translating English non-finite clauses into Vietnamese.